2014
DOI: 10.1016/j.rmed.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indacaterol on arterial blood gases in patients suffering from acute exacerbation of COPD

Abstract: Indacaterol up to 300 μg is a potent bronchodilator that may induce small, transient decrease in PaO2 mainly in patients with relatively well-preserved PaO2. There appeared to be no clinical consequences of these PaO2 abnormalities in patients suffering from AECOPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A proof of concept [ 44 ] performed in AECOPD patients having a mild-to-moderate worsening of dyspnea demonstrated that an early treatment with doubling dose of a combination of a LABA (Salmeterol) plus an inhaled corticosteroid (ICS, Fluticasone Propionate) for 10 days has a potential effect avoiding the requirement of prednisone within 30 days of the onset. In a single-center, open-label, randomized, crossover, and single-blind trial on 12 hospitalized AECOPD patients, a recent study exploring the acute effect of indacaterol found a significant mean increase in FEV 1 and forced vital capacity (FVC), with the highest increase at the dose of 300 mg; however, transient episodes of oxygen desaturation were observed in some patients with relatively well-preserved PaO 2 (− 5.9 mmHg [95% CI -1.4 to − 10.4] and − 6.2 mmHg [95% CI -2.7 to − 9.8] in the mean peak in PaO 2 over 6 h in the group treated with indacaterol 150 mg and indacaterol 300 mg, respectively) [ 45 ]. Similar increases were observed when indacaterol was administered over 5 days in the emergency department in comparison to salbutamol [ 46 ].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…A proof of concept [ 44 ] performed in AECOPD patients having a mild-to-moderate worsening of dyspnea demonstrated that an early treatment with doubling dose of a combination of a LABA (Salmeterol) plus an inhaled corticosteroid (ICS, Fluticasone Propionate) for 10 days has a potential effect avoiding the requirement of prednisone within 30 days of the onset. In a single-center, open-label, randomized, crossover, and single-blind trial on 12 hospitalized AECOPD patients, a recent study exploring the acute effect of indacaterol found a significant mean increase in FEV 1 and forced vital capacity (FVC), with the highest increase at the dose of 300 mg; however, transient episodes of oxygen desaturation were observed in some patients with relatively well-preserved PaO 2 (− 5.9 mmHg [95% CI -1.4 to − 10.4] and − 6.2 mmHg [95% CI -2.7 to − 9.8] in the mean peak in PaO 2 over 6 h in the group treated with indacaterol 150 mg and indacaterol 300 mg, respectively) [ 45 ]. Similar increases were observed when indacaterol was administered over 5 days in the emergency department in comparison to salbutamol [ 46 ].…”
Section: Bronchodilatorsmentioning
confidence: 99%
“…However, capsule inhalers are a commonly used devices to efficiently deliver several types of medicaments by inhalation (25,26). In particular RS01 was superior in the aerosolization of FF in terms of drug dispersion and emitted dose compared when the same carrier-based formulation was aerosolized using HandiHaler or Turbospin devices (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, indacaterol, a once-a-day (ultra)-LABA, was found to be effective in improving lung function during an acute exacerbation of COPD at the dose of 300 mg, with an effect that was similar to that obtained with high doses of nebulized salbutamol (1250 mg three times a day) (Segreti et al, 2013), although this caused transient episodes of oxygen desaturation (Rogliani et al, 2014b).…”
Section: B the Role Of Bronchodilators In The Management Of Chronic Obstructive Pulmonary Diseasementioning
confidence: 96%